“HIDING IN THE GULLET ” - A Case Report of Neuroendocrine tumor of supraglottic Larynx with brief Literature Review. - Deepthi A; Manaswini R; Srijanaki M (Tropical Journal of Pathology and Microbiology, 2025)
Laryngeal neuroendocrine tumors(NET) are infrequent tumors of the head and neck comprising <1% of all laryngeal neoplasms1. These tumors are common in elderly men and often occur in supraglottic larynx. They have a wide pathologic spectrum ranging from well differentiated neuroendocrine tumors(NETs) to poorly differentiated neuroendocrine carcinomas(NECs). In this case report we present the occurrence of a grade II Neuroendocrine tumor of supraglottic larynx in a elderly female which is rarely reported in literature.